California County Planning Association Conference at Lake Arrowhead - Watkins, Howard::::::::: (1984)
Floor: Nina Lambert (Butte); Seated: ?, Lillian Rousek, ?, Virginia Causey (Fresno), ?; Back Row: ?, Association's 1st Vice-President Howard Watkins (Fresno), Edwin Rousek (Fresno), ?